Spontaneous omental infarction: A rare case of acute abdomen - Subasinghe, Duminda; Jayasinghe, Ravindri; Ranaweera, G.G.; Kodithuwakku, Uditha (Sage Publishing, 2022)
Omental infarction is a rare but a sinister cause of acute abdomen. Preoperative diagnosis is challenging due to its rare nature. It poses nonspecific abdominal signs that can be easily mistaken with other more common intra-abdominal pathologies. We report a case of a 37-year-old male patient presented with right lower quadrant abdominal pain with an elevation of inflammatory markers. His cross-sectional imaging did not a reveal specific diagnosis; therefore, a diagnostic laparoscopy was performed which revealed a non-inflamed appendix and an inflammatory mass formed by the ischemic omentum attached to the ascending colon. Diagnostic laparoscopy and subsequent laparotomy revealed spontaneous omental infarction. The histology of the resected specimen was in keeping with the omental necrosis. This case reflects the importance of considering omental infarction in patients presenting with abdominal pain and raised inflammatory markers. He made an uneventful recovery following surgery.
Keywords: Acute abdomen; spontaneous omental infarction